2017
DOI: 10.1111/anu.12514
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoside by-product dietary supplementation influences blood chemistry, immune response, oxidative stress resistance and intestinal morphology of juvenile amberjack,Seriola dumerili

Abstract: We explored the influence of nucleoside by-products (NBP) on blood chemistry, immune response, oxidative stress and intestinal morphology of Seriola dumerili. Four experimental diets were formulated where diets 1-3 are semipurified and supplemented with liquid NBP at concentration of 0 (D1, negative control), 30 (D2) and 90 (D3) g/kg. Diet 4 (D4) is a fishmeal-based positive control diet. Each diet was randomly allocated to triplicate groups of fish for 50 days. The results revealed a significant influence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 61 publications
2
6
0
Order By: Relevance
“…In contrast, the results of present study indicated that dietary NT-rich yeast supplementation did not significantly affect T-NOS and T-SOD activities for shrimp. Thus, although there are considerable gaps in existing knowledge about the effects of the NT diets on shrimp's immune responses, it was clear that yeast NT exerted a beneficial effects on immunity in our study, which agrees with previous findings in amberjack (Hossain et al, 2017), common carp (Sakai et al, 2001), olive flounder (Paralichthys olivaceus) (Song, Lim, & Lee, 2012), rainbow trout (Yousefi et al, 2016), red drum (Sciaenops ocellatus) (Cheng et al, 2011), sea bream (Pagrus major) and tilapia (Xu et al, 2015). However, high levels of dietary NT could cause high serum uric acid, toxicological effects and interference with the metabolism of other nutrients in most monogastric animals (Rumsey, Winfree, & Hughes, 1992).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In contrast, the results of present study indicated that dietary NT-rich yeast supplementation did not significantly affect T-NOS and T-SOD activities for shrimp. Thus, although there are considerable gaps in existing knowledge about the effects of the NT diets on shrimp's immune responses, it was clear that yeast NT exerted a beneficial effects on immunity in our study, which agrees with previous findings in amberjack (Hossain et al, 2017), common carp (Sakai et al, 2001), olive flounder (Paralichthys olivaceus) (Song, Lim, & Lee, 2012), rainbow trout (Yousefi et al, 2016), red drum (Sciaenops ocellatus) (Cheng et al, 2011), sea bream (Pagrus major) and tilapia (Xu et al, 2015). However, high levels of dietary NT could cause high serum uric acid, toxicological effects and interference with the metabolism of other nutrients in most monogastric animals (Rumsey, Winfree, & Hughes, 1992).…”
Section: Discussionsupporting
confidence: 93%
“…Serum biochemical parameters in the current experiment were within the normal range for L. vannamei (Cao et al., ; Hu et al., ). TP concentration in serum is the most essential compound and it is important for sustaining a healthy immune system (Hossain et al., ). In the present study, increased serum TP in the NT‐rich yeast‐supplemented diets suggested that dietary NT‐rich yeast may act as an immunostimulant for shrimp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of hematological and biochemical parameters in the blood is a valuable tool that can be used as an effective index to monitor fish health and pathological changes. Both hematological and biochemical parameters obtained in the present experiment were within the normal range for greater amberjack, compared to previous studies [80][81][82]. Most blood parameters studied remained constant along the study and only erythrocytes, protein, cholesterol and amylase were lower at the end of the spawning season.…”
Section: Discussionsupporting
confidence: 71%
“…Little information is available about the immune system of greater amberjack [10,35] and few studies have investigated the use of immunostimulants with this species [36,37,38], with none using MOS or concentrated MOS (cMOS) inclusion. For this reason, the objective of the present work was to determine the effect of MOS and cMOS (Bio-Mos® and Actigen®) and their combination on greater amberjack juveniles, focusing on immune parameters, protective effects against a N. girellae and any impact on growth/feed efficiency.…”
Section: Accepted Manuscriptmentioning
confidence: 99%